Ribosomal mutations cause p53-mediated dark skin and pleiotropic effects - McGowan, Kelly A (2008)
Mutations in genes encoding ribosomal proteins cause the Minute phenotype in Drosophila and mice, and Diamond-Blackfan syndrome in humans. Here we report two mouse dark skin (Dsk) loci caused by mutations in Rps19 (ribosomal protein S19) and Rps20 (ribosomal protein S20). We identify a common pathophysiologic program in which p53 stabilization stimulates Kit ligand expression, and, consequently, epidermal melanocytosis via a paracrine mechanism. Accumulation of p53 also causes reduced body size and erythrocyte count. These results provide a mechanistic explanation for the diverse collection of phenotypes that accompany reduced dosage of genes encoding ribosomal proteins, and have implications for understanding normal human variation and human disease.